MUSLIM STUDENTS’ PERCEPTION OF WESTERN VALUES AS PRESENTED IN ENGLISH TEXT BOOKS: INTERNATIONAL ISLAMIC SCHOOL MALAYSIA (SECONDARY) AS A CASE STUDY1 - Souad, Merah; Ramdane, Tahraoui; Husin, Nor Hayati; Khalid, Madihah; Abu Kassim, Noor Lide; Md. Sidek, Suzana Suhailawaty (2018)
This paper examines the perception of Muslim teachers and students of the values embedded in the English textbooks at the Secondary level of the International Islamic School Malaysia (IISMS). The effect of these values on the students’ vision of an Islamic identity are also analyzed. IISMS offers IGCSE curriculum and uses textbooks written and published in the United Kingdom. It is quite impossible to learn English without delving in its culture. This issue becomes more serious when the textbooks used to teach this language are written in a completely different social and cultural context, alien to the students’ social milieu. Interviews with a number of selected students and teachers were conducted; as well as classroom observations to observe how values are disseminated to students in order to enrich the obtained data. The analysis of the data showed that the Western values embedded in the English textbooks were explicitly and implicitly manifested. The study also showed that there was considerable contradiction between these values and those values propagated in other textbooks used by the same students for other subjects, as well as with values propagated by teachers and parents. It was concluded that Muslim students’ perception of Western values varied between acceptance and rejection.